Regulatory framework in cyber crime laws - Mohd Shariff, Roos Niza (2005)
The technology age has assimilated each and every one of us in one way or another.With the growth and widespread use of technology information (IT), we have witnessed and shared the fruition of its many new applications, e-commerce and business opportunities.There has also been a corresponding upsurge of a new generation of crimes known as cyber crimes.Cyber crimes or computer crimes are harmful acts committed from or against a computer or network or against information on computers or network.This paper attempts to describe the growing danger and rise of cyber crimes throughout the nations since cyber crimes are transnational nature of cyberspace.The highlight will be on the types of cyber crimes and the current laws available to combat these crimes. By understanding the crimes and the laws governing them, we would be able to appreciate some of the common threats that are often neglected or taken for granted.This paper will end with some recommendations to curb the issues raised.